Analysis of stratospheric ozone depletion in the Arctic using a data assimilation technique - Sagi, Kazutoshi (2014)
Serious ozone depletion has been measured every Antarctic spring since the early 80’s. This ozone depletion is considered to be a result of photo chemical reactions and cat- alytic cycles resulting from anthropogenic halogen containing gases. In addition, the formation of Polar Stratospheric Clouds (PSCs) facilitates ozone loss because reac- tive halogen species are released by heterogeneous reactions on the surface of a PSC particle.Generally, Arctic ozone depletion is less severe and show larger variability than Antarctic loss because of the unstable and warmer condition. However, the Arctic stratosphere has been becoming colder during past decades and the Arctic ozone loss in the 2011 winter was comparable to Antarctic losses. Ozone depletion is di- rectly/indirectly linked to the climate because the absorption of UV radiation changes the temperature field. It is therefore important to quantify the loss for future climate prediction.The aim of this thesis is to quantify Arctic ozone depletion in several winters by using the data assimilation technique which is generally used in numerical weather prediction. The DIAMOND (Dynamical Isentropic Assimilation Model for Odin Data) is used in this thesis. This thesis includes two articles. The first paper fo- cuses on the specific northern winter (2009/2010) when SMILES (Superconducting Submillimeter-Wave Limb-Emission Sounder) observed stratospheric species. In Ad- dition, a new vertical transport scheme was implemented into the DIAMOND model to account for the diabatic descent inside the polar vortex during the polar night. The comparison shows that the ozone loss estimation from the assimilation of SMILES agrees with the loss from Odin/SMR (sub-millimeter microwave radiometer) measure- ment. Two different chemical mechanisms, the Cl catalytic cycle with PSC formation and NOx related chemistry, can explain losses at different altitudes that occurred in the 2009/2010 winter. The second paper presents the extension of the assimilation analysis for the entire SMR ...